STRATEGIES FOR INSTILLING RELIGIOUS MODERATION UNDERSTANDING AMONG CHURCH CONGREGATIONS IN INDONESIA - Elianus Waruwu; Diantiwati (PT. Jurnal Center Indonesia Publisher, 2025)
This study highlights the urgent need to instill an understanding of religious moderation among church congregations in Indonesia’s pluralistic society, as a means to reduce religious tensions and extremism. Although the Indonesian government has promoted the concept of religious moderation, its implementation within church communities remains underexplored. This research aims to identify effective strategies for fostering a moderate and inclusive understanding of religious moderation within Indonesian church congregations. A qualitative methodology was employed using a literature review approach based on relevant scholarly sources. Findings indicate that foundational strategies involve strengthening theological understanding of religious moderation from a Christian perspective, emphasizing core teachings such as love as the greatest commandment, Christian hospitality as practical application, and the theological principle of mutual acceptance (Romans 15:7). Furthermore, the study underscores the vital role of churches in this process through inclusive religious education, improved moderate religious literacy, responsible use of social media, engagement in interfaith dialogue, and systematic training programs. Cultivating a moderate and inclusive attitude requires nurturing humility, reinforcing national commitment in line with Pancasila, embracing diversity, rejecting extremism, and actualizing these values in daily life. To overcome challenges, the study recommends effective socialization, enhanced religious literacy, wise media engagement, collaboration with various stakeholders, exemplary leadership, and continuous program evaluation. The study concludes that religious moderation is an essential contribution of the church to national unity, conflict prevention, the upholding of national values, interfaith harmony, and the strengthening of national identity.